Reconstruction of the Nasolabial Fold Using Island Pedicle Flap: A Systematic Approach for Flap Design - Wirya, Andrew Yoshihiro; Kwartantaya, Ketut; Darmaputra, I Gusti Nyoman; Pramita, Nyoman Yoga Maya; Saputra, Herman (Journal of Pakistan Association of Dermatologists, 2025)
Reconstruction of nasolabial defects following wide excision presents both functional and aesthetic challenges. We report the case of a 65-year-old female with basal cell carcinoma in the nasolabial region who underwent a 5-mm wide excision followed by reconstruction using an island pedicle flap. The flap demonstrated excellent viability, and follow-up revealed satisfactory wound healing with minimal scarring. This case highlights the versatility and safety of the island pedicle flap for defect repair in the nasolabial region. Successful outcomes depend on careful flap design with attention to anatomic distortion, vascular supply, technical execution, and aesthetic considerations. The island pedicle flap remains a reliable and effective option for reconstruction of nasolabial defects after tumor excision.